EVALUASI DURASI PROYEK DENGAN METODE PROBABILITAS PADA PROYEK RENOVASI BANGUNAN MES DAN SARANA PENDUKUNG KANTOR BALAI PENGKAJIAN TEKNOLOGI PERTANIAN BALI - Yohana Jusna; I Gede Ngurah Sunatha; Tjokorda Istri Praganingrum (Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
In order for office buildings to always be functional, building maintenance and maintenance activities need to be done both physical maintenance and facilities and infrastructure that support office activities. The process of maintaining and upgrading buildings is inseparable from the role of good project management in planning, implementing and controlling the project itself. in the implementation of the project time and cost greatly affects the success rate of the project. In the mess building renovation project and supporting facilities office of the Bali Agricultural Technology Assessment Center the implementation time is not in accordance with the scheduling made. Therefore, the analysis of the review time of the implementation of the project is important again. in this study the authors used a method of probabilities analysis to determine the age of the project optimistic duration, expected duration and pessimistic duration. with a project success rate of 85% and a failure rate of 15%. Basically, probability theory intends to examine and measure uncertainty (uncertainly) and try to explain quantitatively. Based on the results of the analysis that has been done obtained the results of the duration of optimist, expected and pessimistic of each item with a probability rate of 85% success rate and 15% failure rate of the project on each work item has a duration of 1-3 days from normal time.